PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP BUDGETARY SLACK DENGAN ORGANIZATIONAL COMMITMENT DAN KARAKTER PERSONAL SEBAGAI VARIABEL MODERATING (Studi Empiris pada OPD Kota Pekanbaru) - Riliana, Melvi; Agusti, Restu; L, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This purpose of this research was to identify and analyze about (1) the Influence of budgetary participation to budgetary slack (2) the Influence of budget goal clarity to budgetary slack (3) the Influence of budget participation to budgetary slack with organizational commitment as moderating variable. (4) the influence of budget goal clarity to budgetary slack with organizational commitment as moderating variable. (5) the influence of budgetary participation to budgetary slack with personal characters as moderating variable. (6) the influence of budget goal clarity to budgetary slack with personal characters as moderating variable. The study was conducted on 30 OPD in Pekanbaru city.The data used in this research is primary data with the questionnaire as an instrument. The method that used to the sample selection is purposive sampling. The samples of this research were 90 respondents. Hypothesis test used in this research was statistical t-test. Data analysis technique used in this research is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The result of hypothesis testing shows that budget participation variable has significant effect to budgetary slack with significant value (0,000<0,05). the budget goal clarity has a significant effect on budgetary slack with significant value (0,001<0,05). organizational commitment and personal characters as variables moderating variables has effect to budgetary slack.Keywords : budgetary participation,budget goal clarity,budgetary slack, organizational commitment, personal characters